Climate Change, Agriculture and Food Security in Tanzania - Arndt, Channing; Farmer, William; Strzepek, Kenneth; Thurlow, James (World Bank, Washington, DC, 2013)
The consequences of climate change for agriculture and food security in developing countries are of serious concern. Due to their reliance on rain-fed agriculture, both as a source of income and consumption, many low-income countries are considered to be the most vulnerable to climate change. This paper estimates the impact of climate change on food security in Tanzania. Representative climate projections are used in calibrated crop models to predict crop yield changes for 110 districts in the country. The results are in turn imposed on a highly-disaggregated, recursive dynamic economy-wide model of Tanzania. The authors find that, relative to a no-climate-change baseline and considering domestic agricultural production as the principal channel of impact, food security in Tanzania appears likely to deteriorate as a consequence of climate change. The analysis points to a high degree of diversity of outcomes (including some favorable outcomes) across climate scenarios, sectors, and regions. Noteworthy differences in impacts across households are also present both by region and by income category.